Altruism and morality: some problems for Max U - Hodgson, Geoffrey M. (Frontiers in Behavioral Economics, 2025)
This essay considers some limitations of the assumption of utility maximization (Max U) as an explanation of human action. Leading promoters of the assumption explicitly avoid the question of motivation, to focus instead on manifest behavior. Max U is strictly unfalsifiable. With appropriate assumptions and contextual variables, it can be made to fit any real-world behavior. Max U is neither specifically human nor a product of evolution: it assumes a static set of preferences. Altruism, by definition, can be costly. If those costs result overall in a net disutility, even with a “warm glow” from helping others, then this is incompatible with the Max U assumption, where no voluntary behavior reduces utility. Relevant too are criticisms of “folk psychology,” where behavior is deemed to stem from stable preferences and beliefs. We also need to consider the nature of moral sentiments and how they evolved in cooperative human groups. Overall, an evolutionary perspective enables the development of a richer explanation of human behavior, including moral motivations, altruism and self-interested pursuits.